(untitled) (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2019)
الكبد عضو حساس لا يتحمل تغيرات كبيرة للعوامل البيئية. وهو مؤلف من برانشيما الكبد التي تنقسم بواسطة النسيج الضام إلى فصيصات غير منتظمة, يتوزع فيها النسيج البنكرياسي حيث تتجمع الخلايا البنكرياسية حول فروع الوريد البابي . تنتظم الخلايا الكبدية بشكل شعاعي في حبال حول الوريد المركزي . يتبين لنا أن الشكل النسيجي للكبد وتعضي النسيج البنكرياسي عند الأنواع الغبس Boops boops، الفريدة Pagrus caeruleostictus والسلامورة Pagellus acarne يشابه الشكل العنبي الموجود عند كثير من الأسماك العظمية بما فيها أسماك المياه العذبة والمالحة . الهدف من الدراسة الحالية هو دراسة تحليلية نسيجية للكبد البنكرياسي عند الأنواع الغبس Boops boops، الفريدة Pagrus caeruleostictusوالسلامورة Pagellus acarne من فصيلة Sparidae، بما يخدم لاستخدامها في تحديد درجة القربى بين الأنواع المدروسة. The liver is a sensitive organ that dose not bare a lot of environmental factors changes. It is composed of liver parenchyma which divided by connective tissue in to unorganized lobes in which the pancreatic tissue distributed, where the pancreatic cells gathered around the branches of pyloric vein. The liver cells gathered radically in robes around the central vein. It is clear to us that the liver tissue form and the pancreatic tissue organization in species Boops boops, Pagrus caeruleoticutus and Pagrus acarne ( bony fishes from Sparidae family) resemble the grape shape that found in many marine and fresh water bony fishes. The aim of this present work is analytical and tissues study of the pancreatic liver in Boops boops, Pagrus caeruleoticutus and Pagrus acarne in order to use it in the determination of the relative degree among these species.